2015
DOI: 10.1007/s10072-015-2314-y
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone injection ameliorates cognitive deficits in rat model of Alzheimer’s disease

Abstract: Oxidative stress plays important role in the pathogenesis of Alzheimer's disease (AD). Edaravone is a potent free radical scavenger that exerts antioxidant effects. Therefore, in this study we aimed to investigate neuroprotective effects of edaravone for AD. Wistar rats were randomly divided into three groups (n = 15): control group, model group, and treatment group, which were injected with phosphate buffered saline, Aβ1-40, and Aβ1-40 together with 5 mg/kg edaravone, respectively, into the right hippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…ROS is one of the crucial factors promoting the pathological progression of AD via aggregating the toxicity of Aβ and CCH-driven vicious cycles [23,24]. Previous studies showed that EDA not only had inhibition effects on multiple key AD pathways including Aβ, Tau-hyperphosphorylation, neuroinflammation, neural oxidative stress, and neuronal loss via scavenging both ROS and Aβ in a family AD mouse model [25] but also alleviated Aβ or streptozotocin-induced cognitive impairment via anti-oxidative stress and anti-inflammationin in rat models [26,27] or in invitro models [28,29]. Moreover, recent experimental studies also found that EDA could attenuate cognitive deficits via inhibiting oxidative stress induced by CCH in rat models [18,30].…”
Section: Introductionmentioning
confidence: 99%
“…ROS is one of the crucial factors promoting the pathological progression of AD via aggregating the toxicity of Aβ and CCH-driven vicious cycles [23,24]. Previous studies showed that EDA not only had inhibition effects on multiple key AD pathways including Aβ, Tau-hyperphosphorylation, neuroinflammation, neural oxidative stress, and neuronal loss via scavenging both ROS and Aβ in a family AD mouse model [25] but also alleviated Aβ or streptozotocin-induced cognitive impairment via anti-oxidative stress and anti-inflammationin in rat models [26,27] or in invitro models [28,29]. Moreover, recent experimental studies also found that EDA could attenuate cognitive deficits via inhibiting oxidative stress induced by CCH in rat models [18,30].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, this documented ability of LCM/ND lipid nanoemulsion to function as a carrier of selected small molecular compounds would, of course, be potentially applicable to certain drug molecules already being used in research for treating Alzheimer's disease (and brain injury). Several low-molecular-weight, and sufficiently lipophilic, candidates for incorporation into the LCM/ND lipid nanoemulsion are Edaravone (Jiao et al 2015;Yang et al 2015), caffeine (Chen et al 2010;Chieffi et al 2011;Marques et al 2011;Mohan et al 2015), resveratrol (Turner et al 2015;Zhao et al 2015), and docosahexaenoic acid or DHA Hashimoto et al 2016;Hjorth et al 2013;Mayurasakorn et al 2016;Pan et al 2015;Vandal et al 2014;Williams et al 2013;Yassine et al 2016aYassine et al , 2016b.…”
Section: Transcranial Ultrasoundmentioning
confidence: 99%
“…Edaravone, a potent free radical scavenger with antioxidant effects, may be developed as a novel agent for the treatment of AD for improving cholinergic system and protecting neurons from oxidative toxicity [110]. The mammalian target of rapamycin (mTOR) pathway has been reported to mediate Ab clearance through autophagy and may represent an important therapeutic target for AD [111].…”
Section: Alzheimer's Diseasementioning
confidence: 99%